Ultra-low concentration of chlorine dioxide regulates stress-caused premature leaf senescence in tobacco by modulating auxin, ethylene, and chlorophyll biosynthesis - Huang, Yue (Plant physiology and biochemistry : PPB, 2022)
Copyright © 2022 Elsevier Masson SAS. All rights reserved.